Conflict Management Strategies in Human Resources Management Work Teams - Budi Rismayadi (International Publisher (YAPENBI), 2024)
This research aims to investigate effective conflict management strategies in the context of human resource management (HR) work teams. Conflict in the workplace, especially in HR teams, can be a significant challenge that affects productivity and harmony among team members. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of conflict management strategies in human resource management work teams has a significant positive impact in improving harmonious and productive working relationships in the workplace. By implementing an open communication approach, teams can easily share information, express opinions, and resolve conflicts more effectively. Collaborative conflict resolution also allows team members to work together to find a solution that is satisfactory for all parties involved, thereby reducing the possibility of larger conflicts arising in the future. Additionally, through developing communication skills, team members can improve their ability to listen, express thoughts clearly, and understand others' perspectives, all of which are important aspects of managing conflict wisely.